Parental Divorce and Externalizing Problem Behavior in Adulthood. A Study on Lasting Individual, Family and Peer Risk Factors for Externalizing Problem Behavior when Experiencing a Parental Divorce. Issue 1 (2nd January 2020) - Sillekens, Sacha; Notten, Natascha
ABSTRACT: This study explored the relationship between experiencing a parental divorce in childhood and externalizing problem behavior (EPB) in adulthood. We examined individual, family, and peer influences for those growing up in a broken home. Our findings indicate that growing up in a broken home has enduring consequences for EPB. However, factors influencing EPB in adulthood did not differ according to family structure. Regarding changes in EPB in adulthood, having more deviant friends was more hazardous for those growing up in a broken home, while parental rejection and low self-control were more hazardous for those from an intact family.